Effect of Fluoride-releasing Resin Cement on the Development of White Spot Lesions Around Orthodontic Brackets - A Retrospective Study - Merati Mohsen; Sabzevari Berahman (Wolters Kluwer Medknow Publications, 2024)
Aims This study aimed to assess the effect of G-CEM, a fluoride-releasing cement, on the development of white spot lesions (WSLs) and their severity around orthodontic brackets. Methods and Materials This case-control study was conducted by reviewing 140 dental records of fixed orthodontic patients presenting to an orthodontic clinic. The patients were assigned to two groups (n = 70). In group 1, Transbond XT resin cement, and in group 2, G-CEM had been used for bracket bonding. The frequency and severity of WSLs in each group were evaluated by assessing the available post-treatment photographs of patients and notes left by their orthodontist in their records in this regard. The number of teeth with WSLs in each patient was recorded, and the severity of lesions was categorised by Gorelick's analysis. Statistical Analysis Comparisons were made using independent t-test, Wilcoxon test and Mann-Whitney test (alpha = 0.05). Results In both the maxilla and mandible, the prevalence of WSLs was significantly higher in the Transbond XT group than in the G-CEM group (P = 0.01). The difference in frequency of WSLs between the maxilla and mandible was not significant within each group (P > 0.05). Tooth #22 had the highest frequency of WSLs (11.4%) in the Transbond XT group, while teeth #12 and #36 had the highest frequency of WSLs (2.9%) in the G-CEM group. The difference in frequency of WSLs was not significant between males and females (P > 0.05). Conclusion Bracket bonding with G-CEM fluoride-releasing cement significantly reduced the development of WSLs around orthodontic brackets.